Effect of fermentation time on dietary fiber content, total sugar content, and organoleptic quality of Jali Tape (Coix Lacryma-Jobi L) - Anisa Nurul Syafitri; Tria Astika Endah Permatasari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The prevalence of diabetes mellitus (age >15 years) is 1,8% and is increasing every year in Indonesia. Jali seeds (Coix lacryma-jobi L) are known to contain good dietary fiber for people with DM. One of the processed foods from jali seeds is tape. Therefore, tape jali can be used as an alternative snack food for patients with DM. The aim of this study was to determine the effect of fermentation time on the food fiber content, total sugar content, and organoleptic quality of jali tapes. This study was conducted using a Completely Randomized Design (CRD) method. The organoleptic test was carried out in May 2023 by 30 semi-trained panelists from the Nutrition students of the Faculty of Medicine and Health, Muhammadiyah University, Jakarta. Tests for food fiber content and total sugar content were carried out at the PT Saraswanti Indo Genetech laboratory with one control factor, three treatments (48, 72, and 96 h fermentation), and five replications. Organoleptic tests included hedonic quality and liking (hedonic) tests using the questionnaire method, food fiber content tests using the enzymatic-gravimetric method, and total sugar content tests using the Luff Schoorl method. The Kruskal-Wallis and Mann-Whitney tests were used for data analysis. The results showed that there were differences in each sample for the quality of aroma, sour taste, sweetness, and texture (p <0,05), and the sample that was most liked by the panelists was TJ2. Laboratory test results showed that the sample with the highest fiber content and lowest total sugar content was TJ2, at 5,72% and 19,1%, respectively. In conclusion, fermentation time has an effect on the dietary fiber content, total sugar content, and organoleptic quality of jali tape.